Identification of the Zn substitution sites in La-Zn substituted SrAl12O19 from Al-27 solid-state NMR studies - Baby, Bindhu; Dey, Krishna K.; Ajithkumar, Thalasseril G.; Joy, Pattayil A. (Journal of the American Ceramic Society, 2014)
The La-Zn substituted hexagonal strontium aluminate, Sr1-xLaxAl12-xZnxO19, with the magnetoplumbite structure and having five different coordination environments for Al with different symmetries, is investigated using Al-27 solid-state NMR to get detailed information on the sites of substitution of Zn and the associated changes in the local coordination environments of Al. The objective of the study was to get information on the local structural variations in the isostructural La-Co substituted strontium ferrite, Sr1-xLaxFe12-xCoxO19, showing enhanced magnetic performance on substitution. The NMR studies on the aluminate give direct evidence for the sites of substitution and the changes in the local coordination environments. It is found that Zn is substituted at the 2a and 4f(2) AlO6 octahedral sites. However, an interesting observation from the NMR studies is the stabilization of the Al site occupancy at the penta-coordinated 2b site over the distorted tetrahedral 4eAl site, without any substitution at these sites. Large changes in the quadrupolar coupling constant of the 2a and 4e sites are observed between x=0.2 and 0.3, corresponding to the compositional region showing higher performance in the case of Sr1-xLaxFe12-xCoxO19, indicating the role of distortion of local coordination environments on suitable substitution in controlling the performance parameters.